Interventions Designed to Improve Adherence to Growth Hormone Treatment for Pediatric Patients and Their Families: A Narrative Review - Selina Graham; Sophia Quirke-McFarlane; Vivian Auyeung; John Weinman (MDPI AG, 2022)
Even though growth hormone (GH) treatment is still the only active treatment option to correct growth failure and increase stature for patients with GH deficiencies, evidence has shown that non-adherence remains high. The aim of this review was to identify and review the existing interventional strategies that have been designed to address and improve adherence to GH treatment for pediatric patients and their families. An extensive search of several electronic databases was undertaken to identify relevant interventional studies, published in English, between 1985 and 2021. Additional search strategies included hand-searching topic review articles to identify eligible studies. Articles were screened against the inclusion eligibility criteria and data on sample characteristics, intervention features, and key findings was extracted. A total of fifteen interventional studies were included in the review. The interventions identified were divided into two broad categories: novel injection devices, and patient choice of device. In conclusions, this review acknowledges that there is a lack of evidence-based, theory-driven intervention strategies, designed with the purpose of optimizing treatment adherence and improve clinical and psychosocial outcomes.